Hematological changes associated with hepatitis by hepatitis E virus (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The purpose of the study was to find out the changes in the common hematological parameters in patients (n=998) of acute viral hepatitis caused by hepatitis E virus from April to May, 2018. The mean hemoglobin level was 13.5 g/dL. However, seven patients were found to have hemoglobin level